Brexit Referendum and Business Investment in the UK - Gornicka, Lucyna (Washington, D.C. : International Monetary Fund, 2018)
In this paper I apply firm-level analysis to examine how the Brexit process has affected business investment in the UK. An interaction term of potential trade costs after exiting the EU and a measure of firms' participation in global trade is used as a proxy for firm-level exposure to Brexit-related effects. The results suggest that potential trade costs have had a considerable and statistically significant negative impact on firm investment in the UK after the referendum. At the same time, the post-referendum sterling depreciation has likely contributed positively to investment expenditure by more foreign-oriented firms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Brexit; Business Investment; Firm; Investment; WP; United Kingdom